Antenatal care service satisfaction and associated factors among pregnant women at public health facilities of Wogera district, Northwest Ethiopia: a cross-sectional study - Belachew, Asrat Kassaw; Debie, Ayal; Geberu, Demiss Mulatu; Dagnew, Abinet; Bitew, Gedamnesh; Dejene, Tadesse Mamo; Walle, Agmasie Damtew (Frontiers in Global Women's Health, 2024)
Background: Pregnant women's satisfaction with Ante-Natal Care (ANC) is crucial for improving its quality and providing standardized healthcare services. However, studies on pregnant women's satisfaction with antenatal care and associated factors are limited in Ethiopia, particularly in the study area. Therefore, this study aimed to assess satisfaction and associated factors among pregnant women receiving antenatal care in Wogera district.Methods: A facility-based cross-sectional study was conducted in Wogera district from March to April 2024. A total of 458 pregnant women who attended ANC at health facilities were included in the study. Interviewer -administered structured questionnaire was used to obtain the necessary information for this study and systematic random sampling was used to select the study participants. Multivariable and binary logistic regression analysis was used to identify the effect of each independent variable on the outcome (satisfaction).The overall satisfaction of antenatal care services among pregnant women was 92.1% (95%CI: 89.5, 94.5%). The majority (98.3%) of them were satisfied by the provider's greeting and 97.8% were satisfied by the cost of service but pregnant women were less satisfied by waiting time to see the health workers, cleanness of the toilet, and water supply. Satisfaction of pregnant women was associated with housewife occupational status [AOR= 3.